Maintaining Cleanliness and Boosting Local Economy: Waste Bank's Role in Pohijo Village Development - Febrian, Shela; Nurhidayat, Saiful; Sumardin, Tio; Yahya, Aisyi; Sari, Sindi; Haryvalen, Aqiqo (CV. BImbingan Belajar Assyfa, 2024)
Waste banks represent a strategic approach to implementing the 3R (Reuse, Reduce, Recycle) principles in community-level waste management, incentivized economically. The Waste Bank in Pohijo Village, operational since 2021, is the focus of this study. This research aims to identify the factors influencing community participation in the Waste Bank of Pohijo Village. Utilizing an analytical survey with a cross-sectional design, this study explores the waste bank's role in maintaining environmental cleanliness and boosting the local economy. Given population growth and changing consumption patterns, waste issues increasingly threaten ecosystem balance and human health. The waste bank concept emerges as a sustainable solution that melds waste management with community empowerment. This research highlights how the Pohijo Village Waste Bank enhances environmental cleanliness through community-driven waste collection, sorting, and management. Moreover, it underscores the waste bank's positive economic impact, offering residents income opportunities through waste management and recycling. By examining cross-sector collaboration, community participation, and resultant economic benefits, the study provides insights into how waste banks can drive sustainable change at the village level, yielding long-term environmental and economic advantages. The findings reveal significant community engagement and economic benefits, suggesting that waste banks can be pivotal in fostering sustainability.